Aplikasi metode pemikiran sistem dalam isu polemik antara nas dan maslahah: Kajian menurut perspektif Maqasid al-Shariah / Ahmad Badri Abdullah - Ahmad Badri , Abdullah (2017)
A survey on the contemporary Islamic legal discourse identifies the establishment of a tendency which attemps to grant preponderances on the element of benefits (maṣlaḥah) over Islamic legal texts (naṣṣ). Such an approach owes its inspiration and origin from classical discourse, depicted however in new forms, among others by the attempt to reevaluating the authority of divine textual sources among specific categories of Muslims scholars namely the modernists and postmodernists. Such a phenomenon somehow has triggered confusions among Muslims communities since the abovementioned thinkers daringly criticise normative legal rulings which are formulated from the categorical textual sources. Therefore, this research aims to evaluate polemics instigated by the modernists and postmodernists particularly in issues pertaining to the dialectical relation between benefits (maṣlaḥah) and (naṣṣ) from the framework of maqāṣid al-sharīʿah and systems thinking. Hence, it adopts systems thinking methods that emerged in the contemporary scientific fields in the way to face the modernist and postmodernists tendencies particularly to cater polemics emanated from the dialectical relation. These methods are suitable to effectively explicate the overarching relation between texts (naṣṣ), benefits (maṣlaḥah) and the higher Shari’ah objectives (maqāṣid al-sharīʿah) as well as in offering a holistic view on the three elements in term of their functional roles. Moreover this research employs systems thinking tools in the pursuit of analysing approaches taken by classical scholars in comparison to that of the modernists and postmodernists in dealing with issues which involve the dialectical polemic between benefits (maṣlaḥah) and texts (naṣṣ). In doing so, this research applies a library research in collecting relevent data from both classical and contemporary literatures which are analysed through inductive, deductive as well as comparative methods. The result shows that the classical scholars’ approaches are commendably systemic in handling legal issues such as women testimony, rights of inheritence, and the implementation of Islamic criminal punishments compared to that of the modernists and postmodernists which are rather atomistic. This is due to the fact that, in resolving the issues, those scholars attempt to find a correct balance between attaining societal benefits and safeguarding the original teachings in the texts. Furthermore, the research also identifies parallel characteristics and concerns in both maqāṣid al-sharīʿah and systems thinking by which the symbiosis of both is elementary in the pursuit of managing the relation between religious texts and benefits.